„Reportaż z głębi wieków”, czyli o liryce Konstandinosa Kawafisa - Tuszyńska-Maciejewska, Krystyna (Scripta Neophilologica Posnaniensia, 2019)
„Reportaż z głębi wieków”, czyli o liryce Konstandinosa Kawafisa